Groundwater Level Distribution in Vacuum Dewatering Method in Phreatic Aquifer - Feng Huang; Jianguo Lyu; He Gao; Zhaoteng Yu (Geofluids)
Vacuum dewatering method has been widely used in geotechnical engineering. However, there is little research on the groundwater level distribution under the effect of vacuum pressure which is generated by vacuum wells. In view of this, the groundwater level distribution in phreatic aquifer is analyzed. First, the vacuum pressure distribution in soil is analyzed through Darcy’s law and steady-state seepage control equation based on established particles and pores model. Second, the boundary conditions are modified by the vacuum pressure distribution law and then the water level distribution equations in flow boundary and waterhead boundary conditions are derived. Finally, dewatering experiment is carried out to analyze the water levels in vacuum and nonvacuum dewatering and verify the theoretical model of water level distribution in vacuum dewatering. The results show that, in both boundary conditions, the water levels in vacuum dewatering are lower than those in nonvacuum dewatering. The theoretical values agree with the experimental values well, which proves the rationality of theoretical equations and predicting the water levels in vacuum dewatering method.